Strategi Penerjemahan Pidato Politik - Pamungkas, Muhammad Ersan Pamungkas (Jurnal Penerjemahan, 2020)
This research aims to demonstrate translation techniques adopted by the two translators – Indonesian native speaker and English native speaker in translating five political speeches from Indonesian into English. The research is one by using corpus-based approach, a comparative mode, and translation strategy theories. A qualitative method in the form of a text analysis as a case study is adopted in this research. Analysis of a translation as a product is based on the translation strategies adopted by the the two translators in translating political speeches. The research shows that the two translators apply the same translation strategies. Four methods adopted by the two translators are literal translation method, faithful translation method, semantic translation method, and communicative translation method. The adoption of these four methods also signify two translation ideologies in their translations. In the meantime, nine translation techniques adopted by the two translators are transferensi, calque, literal, cultural equivalence, established equivalence, transposition, modulation, reduction and addition. Keywords: political speech, translation of political speech, translation strategies, translation ideologies, translation method, translation technique.